Quality Characteristics and Αlpha-Tocopherol Content of Shea Butter Samples from Selected Markets Within Three Southwestern States of Nigeria - Adejumo, Olufunmilayo Ebunoluwa; Edun, Temilade Arinola; Kolapo, Adelodun Lawrence; Ayodele, Olatunde Adekunle (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Shea (Vitellaria paradoxa) butter samples from selected markets in Nigeria were analyzed for AOAC quality characteristics and α-tocopherol content. The α-tocopherol was determined by RP-HPLC and mg per serving and % daily values (% DV) were estimated. The ranges of acid value (AV) [mgKOH/kg], free fatty acid (FFA) [%], peroxide value (PV) [meqO2/Kg], iodine value (IV) [gI2/100g] and saponification value (SV) [mgKOH/g] were 2.20- 2.59, 1.15-1.30, 0.75-0.95, 44.43-47.85 and 170.08-259.30, respectively. The -tocopherol had a retention time of 3.561 minutes and its content ranged from 1.15-2.60 mg/100 g in the samples, but 5.25 mg/100 g for the laboratory sample. Milligram (mg) per serving and percentage dietary value were 0.16-0.74 and 1.07-4.93, respectively. Quality characteristics varied significantly (p < 0.05) both within and across different markets. Based on the PV and IV results, the marketed shea butter samples may be both food and industry-grade but failed the FFA test. Similarly, 40% of samples did not qualify for domestic consumption and food industry applications. Hence, the samples with <5% DV values cannot serve as dietary sources of α-tocopherol. Dhaka Univ. J. Pharm. Sci. 21(2): 105-115, 2022 (December)